Educational leadership in education development centers: A qualitative study - Mansoureh Taghavinia; Mohammad Reza Maleki; Kamran Soltani Arabshahi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Education development centers (EDCs) have a vital role in improving the quality of medical education. This study was conducted with the aim of discovering educational leadership characteristics in EDCs. MATERIALS AND METHODS: This study was carried out with a qualitative approach and using a conventional content analysis method. The sampling was purposive. Twenty-four faculty members, managers, and experts of EDCs in the universities of medical sciences included 13 males and 11 females participated in this study. Semi-structured interviews were utilized for data collection. The conventional content analysis approach was utilized to analyze the data. RESULTS: From the data analysis, two categories included "personality characteristics" and "job characteristics" and six subcategories included reliabilism, humanness and altruism, accountability, decisiveness, dynamism and perfectionism, and knowledge, experience, and expertise and 24 codes were extracted. CONCLUSION: Results obtained in the present study will help to increase the awareness of the educational leaders of the EDCs in improving their personality and job skills and this will lead to the qualitative development of educational leadership.